WISDOM AS MOTIF IN FOLKTALES THE GOOD PEASANT’S SON - Abu Fanani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
In this article, the writer discusses wisdom as motif in fourfolktales from four different cultures which are as follows: the GoodPeasant’s Son (A Russian folktale), the Crocodile and the Hunter (anAfrican-Nupe folktale), Breaking the Chain (a Guatemalan folktale),and Wisdom for Sale (an Indian-Gujerati folktale). The writer thendiscusses the wisdom through the actions of the main characters in thethree folktales whilst the words of the main character in one folktale.Further, the writer uses formulaic theory as the aforesaid folktaleshave been spread through the words of mouth from generations togenerations. Yet, the writer has found out the oral stories in writtenbooks. Eventually, the writer draws conclusion that wisdom hasexisted in the four mentioned folktales.